(untitled) (Heritage, 2021)
The adoption of words of foreign, English, origin can be characterized as a common social phenomenon. As it is necessary to understand unknown words and expressions in order to experience literary values, preparing a teacher for interpreting a text implies anticipating the projection of students in the field of vocabulary, semantics and phraseology. Anglicisms can often be understood as unreasonably used words that can slow down the process of experiencing and receiving literary and artistic texts. Precisely because of that, the main research goal is reflected in the examination of the understanding of words borrowed from the English language in the teaching of literature in the fourth grade. The research was conducted on a sample of 80 fourth grade students from elementary schools in Kosovska Mitrovica and Zvečan. The data obtained in the research indicate that students have a poor understanding of borrowed words and that their understanding depends on the school that the student attends and the material status of the family. Students whose families are of better material status have higher scores on the English language comprehension test. The obtained data partially confirm the research hypotheses